Improving critical thinking through OIDDE learning model on batik material in Class VIII-J SMPN 03 Batu - Arifin, Samsul; Iriaji, Iriaji (Imaji: Jurnal Seni dan Pendidikan Seni, 2025)
Learning batik can enhance students’ critical thinking skills, but many students still struggle to describe, analyze, and solve problems effectively, which hinders the achievement of learning objectives. This study aims to improve the learning process and critical thinking of students through the OIDDE learning model that focuses on batik content. This study uses classroom action research, the Kemmis and McTaggart model. The study was conducted starting with pre-action, cycle I, and cycle II. Each cycle includes the planning, action, observation, and reflection stages. The research subjects were 32 students. Data were collected through interviews, observations, questionnaires, tests, and documentation, and analyzed using qualitative descriptive methods supported by quantitative data. The results of the study showed that (1) the learning process was carried out according to the syntax of the OIDDE learning model, there were improvements made in cycle II based on reflections from cycle I, and (2) students’ critical thinking increased significantly, from 28.1% in the pre-action stage to 65.6% in cycle I, and 83.75% in cycle II. These results indicate that the OIDDE model is effective in improving students’ critical thinking skills in learning batik material.